Evaluación de las diferentes estrategias de aprovechamiento de la pulpa de café en la finca la Lindosa, Palermo, Huila, Colombia. (2022)
This monograph will develop the evaluation of the different strategies for the use of coffee pulp for the La Lindosa coffee farm located in the municipality of Palermo-Huila, in order to reduce environmental impacts and promote the importance of reusing said residue. in the coffee zone. To do this, initially a description of the current situation of coffee production in Colombia is made, in order to determine the amount of coffee produced and exported in recent years, cultivated area, existing species, benefit processes used and waste. generated in the process. Next, a diagnosis of the La Lindosa farm is carried out, in which the description of its most relevant aspects is presented, such as its characterization, that is, its location, the hectares it has cultivated and its production process. To finalize the diagnosis, an analysis of the political, economic, social and technological factors that are involved in Colombia and in the department of Huila is carried out.